Metabolomics study of osteopetrosis caused by CLCN7 mutation reveals novel pathway and potential biomarkers - Chen, Xi; Wang, Ziyuan; Fu, Wenzhen; Wei, Zhe; Gu, Jiemei; Wang, Chun; Zhang, Zhenlin; Yu, Xiangtian; Hu, Weiwei (Frontiers in Endocrinology, 2025)
CLCN7 mutation caused abnormal osteoclasts, resulting in osteopetrosis. Depending on the type of mutation, CLCN7 mutations can lead to severe or relatively benign forms of osteopetrosis. However, the serum metabolic alterations in osteopetrosis caused by CLCN7 mutation are still unknown. We aimed to investigate the differences in the metabolome of osteopetrosis patients caused by CLCN7 mutation versus healthy controls (HC), uncovering potential subtype diagnosis biomarkers. 19 osteopetrosis patients caused by CLCN7 mutation and 19 HC were recruited for liquid chromatography-tandem mass spectrometry analysis. Three metabolic pathways were significantly enriched, including glycerophospholipid metabolism (P=0.036948), arachidonic acid metabolism (P=0.0058585) and linoleic acid metabolism (P=0.032035). Ten differential expressed metabolites were located in these three pathways and classified ability with areas under the curve over 0.7 in receiver operating characteristic analysis, suggesting a certain accuracy for being the potential biological markers. Especially, we found that the proteins in glycerophospholipid metabolism were predicted to interact with ClC-7 and further verified that the expression of coding genes were significantly up-regulated in myeloid cell specific Clcn7 G763R mutant mouse. This study provides data on serum metabolomics in osteopetrosis caused by CLCN7 mutation and provides new potential metabolic markers and pathways for diagnosis and pathogenesis of osteopetrosis.